ADULT EFL STUDENT ATTITUDES TOWARD PERFORMANCE-BASED ASSESSMENT - Munawarah; Sukri Adani; Zuhri Efendi (Nusantara Hasana Journal, 2023)
Performance-based assessments such as portfolios, presentations, and participation are now widely used in many English language education programs in public and private universities. There is significant research in the literature on teachers' attitudes toward these types of assessment approaches, but few have explored students' views on these types of assessment techniques. The aim of this study was to find out the attitudes of adult students towards performance based assessments and traditional tests and to see the relationship between length of study and performance based assessments and tests. This research applied a questionnaire to explore the opinions of adult English students (N=110) regarding performance-based assessments (portfolios, presentations and participation) and traditional types of test assessments. The quantitative findings indicate that the four forms of assessment were positively perceived by the participants in this study. The analysis of the background variables revealed that the length of the study had an interactive effect on students' opinions regarding this assessment method. Other background characteristics did not influence the students’ attitudes.